Green's Function Method for Self-Adjoint Realization of Boundary-Value Problems with Interior Singularities - K. Aydemir; O. Sh. Mukhtarov (Abstract and Applied Analysis)
The purpose of this paper is to investigate some spectral properties of Sturm-Liouville type problems with interior singularities. Some of the mathematical aspects necessary for developing our own technique are presented. By applying this technique we construct some special solutions of the homogeneous equation and present a formula and the existence conditions of Green's function. Furthermore, based on these results and introducing operator treatment in adequate Hilbert space, we derive the resolvent operator and prove self-adjointness of the considered problem.